Survey of seasonal changes in physical-chemical properties of drinking water in Sefid-allah village of Qom province - Mohammad Reza Hosseini; Reza foladifard (Mashhad University of Medical Sciences, 2019)
Background and purpose: The safe and health drinking water is one of the vital factors of human life. The reason for this issue is the existence of various strict standards as WHO and EPA in the world and 1053 standard in Iran in the recent years. This study was implemented to evaluate the effect of seasonal changes (spring and autumn) on the physical and chemical properties of drinking water in Sefid-allah village of Qom province. Materials and methods: Measurement of physical and chemical indicators was carried out by the rural wastewater organization of Qom from the potable water sources of Sefid-allah village in two seasons spring and autumn 1390 and 1391. Analyze of parameters like pH, Turbidity, EC, Hardness, CL, NO3−, NO2− , PO34−, NH3, SO42−, F−, CO32−, HCO3−, Ca2+, Mg2+, Na+, K+ and Mn2+ was done according to the standard methods of drinking waters (1053 standard). Results: The mean of residual chlorine, Turbidity, pH, TDS, Total Hardness and Alkalinity reported 0 (mg/lit), 0.995 (NTU), 7.41, 1037.5 (mg/l), 478 (mg/l) and 288 (mg/l, respectively. The results showed that, in among Cations and Anions there are the following sequence was established: Na+> Ca2+> Mg2+> K+ and SO42− > HCO3− > CL− > NO3− > F− > PO34−> NO2− > NH3- HCO3−, respectively. The concentration of pH, HCO3− and Mn2+ were higher than the limited value of the standard. As such, only the concentration average of Turbidity, Ca2+, Na+ and K+ in spring were more than autumn. Conclusion:In conclusion, shift in seasons caused changes in some of the indicators under review. Finally, was found that the quality of drinking water of Sefid-allah village, by correcting some of the parameters, there is no problem for used to drinking water.